Evaluation of the Implementation of Additional Lesson’s Provision at SMA Negeri 3 Banyuasin III, Banyuasin Regency - Rachmawati, Leka; Fitria, Happy; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2024)
This study aimed at knowing and evaluating the implementation of giving additional lessons at SMA Negeri 3 Banyuasin III in the Banyuasin Regency. This study was a descriptive qualitative research. The subjects of this study were the headmaster, vice headmaster, two teachers, and twelve students at SMA Negeri 3 Banyuasin III. The techniques of collecting data were observation, documentation, and interview. The techniques of analyzing data were done in three stages that were (1) Reducing data; (2) Presenting data; and (3) Concluding data. The result showed that the implementation of giving additional lessons at SMA Negeri 3 Banyuasin III in Banyuasin Regency took place well. However, there were some obstacles to the Implementation such as less funding and infrastructure.